USING PODCASTS TO IMPROVE LANGUAGE PROFICIENCY FOR ENGLISH AS A FOREIGN LANGUAGE STUDENTS - Suseno, Edy (Innovare Journal of Social Sciences, 2024)
To communicate their ideas to one another, students use language. They require linguistic proficiency to improve their fluency. Still, a lot of English as a foreign language students struggled to communicate their intentions to other language users. They require a way to facilitate the development of their language proficiency. The application that offers real content is podcasts. By employing them, the pupils can improve their linguistic abilities. The content includes various dialects, speech patterns, and languages. Learning about those resources helps students become more natural and fluid in their speaking. Furthermore, the resources offered in the areas of news, narrative, self-improvement, linguistic variety, voice, accents, and speaking styles facilitate the students in improving their language proficiency. Students’ vocabulary, problem-solving techniques, capacity for introspection, and language proficiency all increase as a result. Through a literature review of the textual content to improve language acquisition, it is determined that using podcast materials helps students improve their speaking, reading, writing, and listening skills. Teachers can use this type of research to their advantage by applying it to the teaching of related disciplines. It also encourages further investigation into similar subjects by other scholars